2022
DOI: 10.4244/eij-d-21-00415
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preprocedural biological markers on 10-year mortality in the SYNTAXES trial

Abstract: Background: Creatinine clearance (CrCl) is an independent determinant of mortality in predictive models of revascularisation outcomes for complex coronary artery disease.Aims: This study aimed to investigate the impact of preprocedural biological markers on 10-year mortality following coronary revascularisation. Methods:The SYNTAX Extended Survival (SYNTAXES) study evaluated the 10-year vital status followup of 1,800 patients with de novo three-vessel (3VD) and/or left main coronary artery disease (LMCAD) rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…In 2021, Hara et al reported that pre-procedural biological parameters, such as CRP and Hb were associated with 10-year mortality post-revascularization, regardless of revascularization technique. [16] In our study, the ML model was built using a combination of baseline clinical characteristics, biochemical and imaging parameters and unconventional potentially important prognostic factors, such as pulmonary hypertension, CRP, Hb, carotid disease, and total occlusion which were all found to play a key role in predicting 5-year all-cause death.…”
Section: Extensive Approach and Unconventional Risk Factorsmentioning
confidence: 99%
“…In 2021, Hara et al reported that pre-procedural biological parameters, such as CRP and Hb were associated with 10-year mortality post-revascularization, regardless of revascularization technique. [16] In our study, the ML model was built using a combination of baseline clinical characteristics, biochemical and imaging parameters and unconventional potentially important prognostic factors, such as pulmonary hypertension, CRP, Hb, carotid disease, and total occlusion which were all found to play a key role in predicting 5-year all-cause death.…”
Section: Extensive Approach and Unconventional Risk Factorsmentioning
confidence: 99%
“…Inclusion of biological markers into the SSII-2020 did not significantly improve predictivity. 20 As is discussed later in contrast to the SSII-2020, machine learning (ML) algorithms identified CRP as one variable able to predict 10-year mortality ( Table 3 ).
Figure 8 All-Cause Mortality at 10 Years With Respect to Biological Markers Mortality rates according to (A) C-reactive protein (CRP), (B) hemoglobin, (C) HbA1c, (D) creatinine clearance (CrCl), (E) triglycerides (TG), (F) low-density lipoprotein cholesterol (LDL-C), and (G) high-density lipoprotein cholesterol (HDL-C).
…”
Section: Section 3: Post Hoc Analysesmentioning
confidence: 99%